2021
DOI: 10.3389/fmed.2020.614827
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Burden of Chronic Obstructive Pulmonary Disease in the Commonwealth of Independent States: Systematic Review and Meta-Analysis

Abstract: Background: Population-based studies from the Russian Federation and neighboring countries on the occupational burden of chronic obstructive pulmonary disease (COPD) are seldom or not included in the systematic reviews. The aim of this review was to summarize published population-based studies from the Commonwealth of Independent States (CIS) in order to ascertain the occupational burden of COPD.Methods: We systematically searched www.elibrary.ru and PubMed for population-based studies on the epidemiology of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
4
Order By: Relevance
“…Respiratory diseases as the leads in the occupational burden in our nickel electrolysis workers 18 are consistent with the overall assumption that aerosol inhalation is the dominating occupational exposure in this industry 19 . Exposure to vapors, gases, dusts and fumes has been demonstrated to explain a significant fraction of respiratory disease in a population since long time ago 20 ; however, it is only recently that studies from the Russian Federation emerged in the English literature 21 . Population attributable fraction % (PAF%) found is this meta-analysis and equaled 6%, was indeed an underestimate of the burden of occupational respiratory disease because of the likely exposure classification bias, when exposure may be underestimated or reported inaccurately.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory diseases as the leads in the occupational burden in our nickel electrolysis workers 18 are consistent with the overall assumption that aerosol inhalation is the dominating occupational exposure in this industry 19 . Exposure to vapors, gases, dusts and fumes has been demonstrated to explain a significant fraction of respiratory disease in a population since long time ago 20 ; however, it is only recently that studies from the Russian Federation emerged in the English literature 21 . Population attributable fraction % (PAF%) found is this meta-analysis and equaled 6%, was indeed an underestimate of the burden of occupational respiratory disease because of the likely exposure classification bias, when exposure may be underestimated or reported inaccurately.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown the significance of occupational exposures in asthma and COPD. [9][10][11] JEM showed that nearly half of our participants were exposed to occupational hazards with different prevalence of HMW, LMW and mixed exposure. HMW such as latex, aerosol and plants, LMW such as wood, metals, detergents, isocyanate and mixed exposure such as metal working, fluids, textiles, and agriculture have been shown to induce both asthma and COPD.…”
Section: Discussionmentioning
confidence: 85%
“…Подверженность воздействию вторичного табачного дыма, N (%)* Exposure to environmental tobacco smoke, N (%)* 1284 ( 93) 1181 ( 94) 103 ( 86) использование твёрдого топлива для отопления, N (%)* Use of fossil fuel for heating, N (%)* 384 ( 28) 368 ( 29) 16 (13) использование твёрдого топлива для приготовления пищи, N (%) Use of fossil fuel for cooking, N (%) 65 ( 5) 62 ( 5 60) 26 (22) употребление алкоголя в любом количестве, N (%) Any alcohol use in any amount, N (%) 797 ( 58) 722 ( 53) 75 ( 63)…”
Section: результатыunclassified
“…По данным последнего, наиболее крупного систематического обзора ущерба от указанных профессиональных воздействий в возникновении респираторной патологии, популяционный атрибутивный риск развития хоБЛ от них может достигать 14%, хронического бронхита -13% [12]. В странах бывшего Советского Союза, по данным мировой литературы, этот вопрос изучен недостаточно, лишь немногочисленные исследования уделяли вопросу роли профессиональных факторов в развитии этого заболевания должное внимание, а диагноз был подтверждён соответствующим образом [13].…”
unclassified